Radical writing center praxis : a paradigm for ethical political engagement - Greenfield, Laura (Utah State University Press, 2019)
"Imagining a writing center where directors and staff become agents in active social justice on campus and beyond. Introducing activist concepts and vocabulary challenging writing centers to recognize their complicity with oppressive systems. A call for a process of critical self-reflection and change to an activist paradigm"--Provided by publisher